BUDI PEKERTI DAN TANTANGAN GLOBALISASI: STUDI TENTANG ADAPTASI NILAI TRADISIONAL DALAM LINGKUNGAN YANG TERUS BERUBAH - Auzi, Cahaya; Damanik, Maulidya Hasanah; Br.Perangin-angin, Reh Bungana Bungana; Setiawan, Deny (Universitas Negeri Medan, 2024)
Abstract : Ethics and the Challenges of Globalization: A Study of the Adaptation of Traditional Values in a Changing Environment. The aim of this research is to specifically explore the role of teachers and parents in education and the development of character and manners, especially in carrying out their duties to shape students' attitudes and character. In addition, this study aims to formulate policy recommendations to strengthen the implementation of character education at the national level. This research is a literature study research. Globalization has brought significant changes in various aspects of people's lives, including in terms of character. Some of the main challenges faced regarding character in the era of globalization include: Erosion of Traditional Values; Influence of Technology and Social Media; Commercialization. One example taken to see the success of character adaptation in this era of globalization is that globalization provides benefits to students' social and cultural development. We can see a concrete example that is currently going viral on various social media platforms, that the traditional